Low-Dose Acetylsalicylic Acid in Chronic Subdural Hematomas: A Neurosurgeon's Sword of Damocles - Mongardi, Lorenzo; Dones, Flavia; Mantovani, Giorgio; De Bonis, Pasquale; Rustemi, Oriela; Ricciardi, Luca; Cavallo, Michele Alessandro; Scerrati, Alba (Frontiers in Neurology, 2020)
Background: The possible influence of different antithrombotic drugs on outcome after neurosurgical treatment of chronic subdural hematoma (CSDH) is still unclear. Nowadays, no randomized clinical trials are available. A metanalysis including 24 studies for a total of 1,812 pooled patients concluded that antiplatelets and anticoagulations present higher risk of recurrences. On the other hand, several studies highlighted that antithrombotic suspension, timing of surgery, and resumption of these drugs are still debated, and patients taking these present higher risk of thromboembolic events with no excess risk of bleed recurrences or worse functional outcome. Our assumption is that the real hemorrhagic risk related to antithrombotic drug continuation in CSDH may be overrated and the thromboembolic risk for discontinuation underestimated, especially in patients with high cardiovascular risk. Methods: A comprehensive literature review with the search terms “acetylsalicylic acid” and “chronic subdural x” was performed. Clinical status, treatment, time of drug discontinuation, complications (in particular, rebleeding or thromboembolic events), and clinical and radiological outcome at follow-up were evaluated. Results: Five retrospective studies were selected for the review, three of them reporting specifically low-dose acetylsalicylic intake and two of them general antithrombotic drugs for a total of 1,226 patients. Only two papers reported the thromboembolic rate after surgery; in one paper, it is not even divided from other cardiac complications. Conclusion: The literature review does not clarify the best management of low-dose acetylsalicylic in CSDH patients, in particular, concerning the balance between thromboembolic event rates and rebleeding risks. We do believe that CSDH precipitates the worsening of comorbidities with a resulting increased mortality. Further studies clearly evaluating the thromboembolic events are strongly needed to clarify this topic. In this perspective paper, we discuss the difficult choice of low-dose acetylsalicylic acid (LDAA) management in patients suffering from chronic subdural hematoma (CSDH). The balance between hemorrhagic and thromboembolic risks often represents a sword of Damocles for neurosurgeons, especially when dealing with patients with high cardiovascular risk. No guidelines are currently available, and a survey by Kamenova et al. showed that most neurosurgeons discontinue LDAA treatment for at least 7 days in the perioperative period of surgical evacuation of CSDH, even though recent studies show that early LDAA resumption might be safe. Thrombosis prophylaxis is administered by only 60%, even though patients with CSDH are at high risk of developing thromboembolic complications. We would like to bring attention to this controversial issue.